A dual wideband high gain 2 × 2 multiple‐input‐multiple‐output monopole antenna with an end‐launch connector model for 5G millimeter‐wave mobile applications. Issue 5 (23rd January 2022) - Aghoutane, Bilal; El Ghzaoui, Mohammed; Das, Sudipta; Ali, Wael; El Faylali, Hanan
Abstract: This article presents the design, analysis, and realization of a new printed multiple‐input‐multiple‐output (MIMO) antenna with a very high gain and wide bandwidth for the millimeter‐wave (mm‐wave) 28/38 GHz fifth generation (5G) new radio (NR) applications. The proposed MIMO antenna consists of four identical patch elements in a 2 × 2 configuration to achieve high gain with wide operating bandwidth. The proposed antenna holds an attractive compact size of 31.891 × 37.528 mm 2 . The proposed MIMO configuration is designed on a 0.508 mm thick Rogers‐5870 substrate material with a loss tangent of 0.0009 and a relative dielectric constant of 2.33. An effective technique for folding the feed line and applying a new protruding ground is introduced to obtain good mutual coupling. The fabricated prototype of the proposed antenna is tested to verify the simulation results for the validation of the suggested design approach. The suggested MIMO antenna exhibits −10 dB impedance bandwidth of 2.6 GHz (27.4–30.0 GHz) and 3.3 GHz (36.7–40.0 GHz) to cover the intended frequency range for 5G applications with isolation less than −22 band peak gains of 18 and 14.5 dBi at 27.5 and 38.8 GHz, respectively. To validate the MIMO performance of the proposed antenna several MIMO diversity parameters such as mean effective gain (MEG), envelope correlation coefficient (ECC), and diversity gain (DG) are evaluated. Determined results indicate ECC < 0.001, DG > 9.995, and an average MEG of −3 dB at the operating bands. The proposed antenna exhibits good agreement between the simulated and measured results, which confirm its suitability for forthcoming mm‐wave 5G MIMO systems and services.